IMPLEMENTASI MEDIA KOMIK DALAM MENINGKATKAN HASIL BELAJAR SISWA KELAS VII PADA MATA PELAJARAN SEJARAH KEBUDAYAAN ISLAM DI MTsN 1 BENGKALIS - Khairunnisa, Iqlima; Ritonga, Supardi (Jurnal Ilmiah Pendidikan dan Keislaman, 2023)
This research is motivated by learning problems that generally still apply many lecture methods so that the learning process is less touched. Therefore, it is necessary to use appropriate learning media in improving learning outcomes. Comics are one of the learning media that make students more enthusiastic in the learning process. The purpose of this study is to find out how the implementation of comic media in improving student learning outcomes and to find out how influential comic media is in improving student learning outcomes. This type of research uses quantitative research with an experimental approach. The subjects in this study were grade VII students at MTsN 1 Bengkalis, while the sample of this study amounted to 32 people. Data collection techniques in this study used observation, test and documentation techniques. After collecting field data and test results, then the data is recapitulated and gets the results of research and discussion. So it can be concluded that the implementation of comic media in improving learning outcomes is very effective, this can be proven by the results of 3-stage observations. In the first observation got a percentage value of 33%, in the second observation the observation results increased to 77% and in the third observation results increased to 93%. The results showed that there was an increase in learning outcomes in the implementation of comic media with descriptive statics  calculations obtaining scores of 42.81  for pretest and 70.63 for posttest